SPME-GC-MS and multivariate analysis of sensory properties of cheese in a sack matured with probiotic starter cultures - Kostelac, Deni; Vrdoljak, Marija, agronom; Markov, Ksenija; Delaš, Ivančica; Jug, Tjaša; Gajdoš Kljusurić, Jasenka; Jakopović, Željko, inženjer prehrambenog inženjerstva; Čanak, Iva; Jelić, Marko, molekularni biolog, 1976-; Frece, Jadranka (2020)
Research background. Cheese in a sack is a traditional cheese produced in Croatia. Types of cheese with similar production technology are made in other countries but chemical and microbiological composition varies between regions. Traditionally, cheese in a sack is produced without the addition of starter cultures. Addition of beneficial probiotic cultures to numerous dairy products has documented advantages. Effects that the addition of probiotic bacteria to traditional cheese have on aroma compounds and sensory properties have not been fully investigated. The aim of this study is to determine the sensory properties and differences in the aromatic profiles between cheese samples ripened in a lambskin sack, produced traditionally without the addition of any starter culture, or with the addition of probiotic bacteria.Experimental approach. In this study, cheese in a sack was produced with the addition of probiotic cultures Lactobacillus plantarum B and L. lactis ssp. lactis S1. During ripening volatile aroma compounds were analysed with a solid-phase microextraction gas chromatography-mass spectrometry. Sensory properties were evaluated by trained tasters who are familiar with the traditional taste of the cheese from a sack. The results of aroma composition and taste scores were then compared using factorial and principal component analyses.Results and conclusions. Chromatography showed differences in the composition of aroma compounds and the sensory properties between the cheese produced with Lactobacillus starter cultures and the control cheese, traditionally produced without a starter culture. The addition of probiotic cultures L. plantarum B and L. lactis ssp. lactis S1 resulted in products with better sensory properties and chemical profile of volatile aromatic compounds.Novelty and scientific contribution. This study investigates the usage of naturally present probiotic cultures as starter cultures in cheese in a sack production.
Pozadina istraživanja. Sir iz mišine je tradicionalni sir koji se proizvodi u Hrvatskoj. Sirevi dobiveni sličnom tehnologijom proizvode se i u drugim zemljama, no njihov kemijski i mikrobiološki sastav varira među regijama. Tradicionalno se sir iz mišine proizvodi bez dodatka starter kultura. Dodatak korisnih probiotičkih kultura brojnim mliječnim proizvodima ima dokumentirane prednosti. Učinci probiotičkih bakterija na aromatske spojeve i senzorska svojstva tradicionalnih sireva nisu u potpunosti istraženi. Svrha je ovog istraživanja bila utvrditi senzorska svojstva i razlike u aromatskim profilima uzoraka sira iz mišine, proizvedenog na tradicionalan način, bez dodatka starter kultura, ili uz dodatak probiotičkih bakterija. Eksperimentalni pristup. U ovom je istraživanju sir iz mišine proizveden uz dodatak probiotičkih kultura Lactobacillus plantarum B i L. lactis ssp. lactis S1. Tijekom zrenja su mikroekstrakcijom na čvrstoj fazi pomoću plinske kromatografije-masene spektrometrije ispitani hlapljivi aromatski spojevi. Senzorska svojstva su ocijenili obučeni senzoričari, upoznati s tradicionalnim okusom sira iz mišine. Rezultati ispitivanja arome i senzorskih svojstava su zatim uspoređeni pomoću faktorske analize i analize glavnih sastavnica. Rezultati i zaključci. Kromatografskom su analizom utvrđene razlike u sastavu aromatskih spojeva i senzorskih svojstava sira proizvedenog pomoću starter kultura Lactobacillus i kontrolnog uzorka sira proizvedenog na tradicionalan način, bez dodatka starter kultura. Dodatak probiotičkih kultura L. plantarum B i L. lactis ssp. lactis S1 rezultirao je proizvodima s boljim senzorskim svojstvima i kemijskim profilom hlapljivih aromatskih spojeva. Novina i znanstveni doprinos. Ova studija istražuje primjenu prirodno prisutnih probiotičkih kultura kao starter kultura u proizvodnji sira iz mišine.
Bibliografija: 49 jed.
Summary ; Sažetak.
Keywords: Sir -- Sir iz mišine -- Zrenje sira -- Probiotičke bakterije -- Starter-kulture -- Aromatski profili